2020
DOI: 10.1161/circimaging.119.009901
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Cardiovascular Magnetic Resonance in Cardiac Amyloidosis

Abstract: Background Cardiac amyloidosis (CA) is a disease of interstitial myocardial infiltration, usually by light chains or transthyretin. We used diffusion tensor cardiovascular magnetic resonance (DT-CMR) to noninvasively assess the effects of amyloid infiltration on the cardiac microstructure. Methods DT-CMR was performed at diastole and systole in 20 CA, 11 hypertrophic cardiomyopathy, and 10 control subjects with calculation of mean diffusivity, fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 36 publications
0
27
0
1
Order By: Relevance
“…This might be an advantage compared with the low-rank and rule-based models for studies on pathology accompanied by altered sheet angles, such as dilated cardiomyopathy (DCM), hypertrophic cardiomyopathy (HCM), cardiac amyloidosis, and aortic stenosis. 69,[73][74][75][76]…”
Section: Discussionmentioning
confidence: 99%
“…This might be an advantage compared with the low-rank and rule-based models for studies on pathology accompanied by altered sheet angles, such as dilated cardiomyopathy (DCM), hypertrophic cardiomyopathy (HCM), cardiac amyloidosis, and aortic stenosis. 69,[73][74][75][76]…”
Section: Discussionmentioning
confidence: 99%
“…b Concentric hypertrophy of the ventricular wall is demonstrated in the short-axis view MRI has also been demonstrated to help diagnose cardiomyopathy in ATTR amyloidosis patients [76]. Finally, a recent study suggested the utility of diffusion tensor imaging for the detection of cardiac amyloidosis, including ATTR amyloidosis [79].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Preliminarni rezultati ove inovativne in vivo tehnike upućuju na nove patofiziološke mehanizme i poboljšanu dijagnostiku, pružajući obećavajuće nove dimenzije u procjeni poremećaja srčanog mišića. 22 Registar hipertrofičnih kardiomiopatija (Registar HCMR) uključio je 2755 bolesnika s HCM-om iz 44 centra u 6 država, a uključuje CMR, genske i podatke biomarkera kako bi se poboljšala predikcija rizika. Osnovni podatci identificiraju 2 podskupine bolesnika: grupu s pozitivnim mutacijama sakromera i većom fibrozom na CMR te grupu s negativnim mutacijama sarkomera i manjom fibrozom.…”
Section: Ehokardiografijaunclassified
“…The preliminary results of this innovative in vivo technique suggest novel pathophysiological mechanisms and improved diagnostics, proving a promising new dimension in the assessment heart muscle disorders. 22 The Hypertrophic Cardiomyopathy Registry (HCMR Registry) recruited 2755 patients with HCM from 44 sites in 6 countries, and includes CMR, genetic, and biomarkers data in order to improve risk prediction. The baseline data identified two distinct subgroups of patients: a group with sarcomere positive mutation and more fibrosis by CMR and a group sarcomere mutation negative with less fibrosis.…”
Section: Ehokardiografijamentioning
confidence: 99%